تطورات التقنية المالية وتأثيرها على التعليم المالي الاسلامي = Financial technology developments and their effect on Islamic finance education - M. Alshater, Muneer; Othman, Anwar Hasan Abdullah (King Abdulaziz University, 2020)
The Research aims to identify fintech market developments and its effect on educational requirements and career preparation for work in IFIs and Islamic fintech sector. Using the descriptive approach and the inductive approach we address the changes that occur on business models of financial institutions and the methods of performing tasks and their correlation to educational and training sector of IFI. Of the Results found: There is an increase in fintech companies market share while traditional companies are shrinking in size, new business models are emerging which needs special education and training, there will be no need for the majority of routine tasks done in today’s bank due to automation abilities, researcher recommends developing new fin-tech programs, or update the existing curriculum by embedding more technological knowledge into it, researchers should give more attention to fin-tech research and how IFIs can benefit from the new technology capabilities in developing new business models, product and services.